The impact of learning physical and health care on students' social skills in junior high schools in Sleman district, Special Region of Yogyakarta - Hermawan, Hedi Ardiyanto; Rizkyanto, Willy Ihsan; Yudanto, Yudanto; Nurcahyo, Fathan; Choliz Majid, Nur (Jurnal Pendidikan Jasmani Indonesia, 2025)
The implementation Physical Education Learning will be influenced by various things, both extrinsic and intrinsic and after learning Physical Education, it will also have an impact on various things, including social skills in students. This research of the bachelor physical education program aims to determine the impact of physical education learning on the social skills of junior high schools in Sleman Regency, Yogyakarta. The researcher will use a quantitative descriptive research design using the survey method. The location of this research is in the Sleman Regency, DIY. The population in this study is all students in junior high schools in the Sleman Regency Area, Yogyakarta which was taken by incidental sampling. The number of samples that have been successfully identified is around 500 students. The instrument used is in the form of a questionnaire either by means of a physical questionnaire (manual questionnaire) or online through a google form. The data analysis technique uses a descriptive statistical analysis technique with percentages. The results of the study showed that the distribution of data from 500 respondents was obtained as follows: 46 respondents (9.20%) obtained the very high category, 129 respondents (25.80%) obtained the high category, 122 respondents (24.40%) obtained the medium category, 174 respondents (34.80%) obtained the low category, and 29 respondents (5.80%) obtained the very low category. So, the conclusion is implementation of Physical Education of Junior High School learning in Sleman Regency falls into low category.